Synthesis and analysis of afficiency of algorithm for objects edges detection by maximum likelihood method - Alexandr, Parshin; Yury, Parshin (Mediterranean Conference on Embedded Computing (New Jersey. Online), 2013)
Edge detection algorithm, which takes into account difference in fractal dimensions of object and background, is synthesized by maximum likelihood method. Adaptive algorithm of edge detection is proposed under a priori uncertainty of fractal dimensions values. This algorithm contains correlation dimension estimates which have been evaluated in terms of observable data. Efficiency comparison of different versions of image data reading for different objects edge position regarding reading direction is made. Algorithm analysis is carried out under complete and incomplete a priori information.